Genome-wide identification and multi-dimensional functional characterization of the SIR2 family in Brassica napus L. - Hanbing Hu; Ling He; Rui Chen; Ziheng Jing; Heping Wan; Zilan Xiao; Hongtao Cheng; Chunhong Wu; Xiaoyun Liu (PLoS ONE, 2026)
Silent Information Regulator 2 (SIR2) family proteins are NAD + -dependent histone deacetylases that play key roles in epigenetic regulation, plant development, and stress responses; however, systematic characterization of this family (hereafter SRTs) in the important oilseed crop Brassica napus (rapeseed) remains limited. In this study, we identified 4 SRT genes in the rapeseed genome, designated BnaASRT1/2 and BnaCSRT1/2, based on their homology to Arabidopsis SRTs and chromosomal localization. These genes encode proteins with conserved SIR2 domains, sharing >80% sequence identity and >95% coverage with Arabidopsis SRTs, and exhibit similar subcellular localizations (SRT1s in the nucleus, SRT2s in mitochondria). Phylogenetic and synteny analyses confirmed the evolutionary conservation of rapeseed SRTs, which originated from whole-genome duplication events and were stably inherited from its diploid ancestors ( Brassica rapa and Brassica oleracea ). Structural analysis indicates that gene structure, motifs, and promoter elements related to stress and hormone responses are conserved, although subtle differences in the promoters suggest functional specialization. Notably, GO enrichment and molecular docking assays demonstrated that BnaSRTs possess histone deacetylase activity, with strong binding affinity to key acetylation sites (e.g., H3K9ac). Treatment with the SIRT-specific inhibitor nicotinamide (NAM) significantly elevated histone acetylation levels and altered the expression of genes involved in photosynthesis, metabolism, and stress responses-further supporting BnaSRTs' ole in epigenetic regulation. Furthermore, expression profiling via the BnIR database showed tissue-specific expression of BnaSRTs (e.g., high BnaASRT2 expression in buds, flowers, and siliques) and dynamic responses to abiotic stresses (salt, drought, cold) and hormones (ABA, JA, IAA), with BnaSRT2s showing the most prominent expression changes. Collectively, these findings clarify the evolutionary conservation, structural features, and functional roles of the SIR2 family in rapeseed, laying a foundation for epigenetic improvement of its agronomic traits.